2019
DOI: 10.1039/c9lc00270g
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-on-a-chip: a microfluidic model to study cell response to environmental gradients

Abstract: Limited blood supply and rapid tumor metabolism within solid tumors leads to nutrient starvation, waste product accumulation and the generation of pH gradients across the tumor mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 40 publications
0
58
0
Order By: Relevance
“…The results observed in the tumor-on-a-chip platform demonstrated a correlation between the generation of a necrotic core and the presence of pH gradients. In addition, in a previous study, we observed that oxygen played a minor role in the generation of the necrotic core, leading to a moderate increase in the number of dead cells observed in the distal region ( 13 ). Our platform is permeable to oxygen, demonstrating that MCF7 cells did not generate hypoxia within the microdevice at 30 million cells/ml ( 19 ).…”
Section: Discussionmentioning
confidence: 64%
See 3 more Smart Citations
“…The results observed in the tumor-on-a-chip platform demonstrated a correlation between the generation of a necrotic core and the presence of pH gradients. In addition, in a previous study, we observed that oxygen played a minor role in the generation of the necrotic core, leading to a moderate increase in the number of dead cells observed in the distal region ( 13 ). Our platform is permeable to oxygen, demonstrating that MCF7 cells did not generate hypoxia within the microdevice at 30 million cells/ml ( 19 ).…”
Section: Discussionmentioning
confidence: 64%
“…Therefore, the development of new tools that allow researchers to decipher the complex mechanisms driving immune exhaustion could accelerate the development of next-generation immunotherapies ( 12 ). In this context, our tumor-on-a-chip platform provides a simple and versatile tool to evaluate the effect of environmental stress such as nutrient deprivation, acidic pH, or waste product accumulation ( 13 ). Immune penetration into solid tumors affects tumor evolution and remains an active research area in the immunotherapy community.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, the bleaching mechanism might not only be resulted from the reactive oxygen species produced by zooxanthellae to damaged the coral host cells but also associated with DO, DIC, and nutrition uptaking [15,18,44]. However, in order to fully address this issue, a more in-depth investigation should be conducted in the near future, for example microsensors for detecting chemical substances can be integrated [45,46].…”
Section: Discussionmentioning
confidence: 99%